2022
DOI: 10.5194/acp-22-2191-2022
|View full text |Cite
|
Sign up to set email alerts
|

Sources and processes of iron aerosols in a megacity in Eastern China

Abstract: Abstract. Iron (Fe) in aerosol particles is a major external source of micronutrients for marine ecosystems and poses a potential threat to human health. To understand the impacts of aerosol Fe, it is essential to quantify the sources of dissolved Fe and total Fe. In this study, we applied receptor modeling for the first time to apportion the sources of dissolved Fe and total Fe in fine particles collected under five different weather conditions in the Hangzhou megacity of Eastern China, which is upwind of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…This is probably the most critical cause of seasonal differences in uptake kinetics. Overall, ALWC increases the soluble Fe fraction and promotes the activity coefficients of Fe 2+ in aerosols . Meanwhile, high temperature facilitates Fenton reactions .…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is probably the most critical cause of seasonal differences in uptake kinetics. Overall, ALWC increases the soluble Fe fraction and promotes the activity coefficients of Fe 2+ in aerosols . Meanwhile, high temperature facilitates Fenton reactions .…”
Section: Results and Discussionmentioning
confidence: 96%
“…As shown in Figure S1c, d, the element mapping of PM 2.5 confirmed that Fe appeared uniformly distributed on the surface of summer and winter PM 2.5 . Individual particle analysis showed that about 76.3–81.8% of Fe-containing particles are internally mixed with acidic secondary aerosols, implying that the wet surfaces of particles promote the heterogeneous reactions between iron ion and acidic species . Additional measurements on the TMIs-H 2 O 2 aqueous reactions or interfacial reactions over a wide range of ionic strengths and compositions are necessary to evaluate the relative importance of these two pathways to H 2 O 2 uptake by PM 2.5 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the term bioaccessible Fe is used for water-soluble Fe in aerosols, which is more bioavailable than insoluble forms such as crystalline Fe oxides in soils. Compared to the lithogenic Fe, the anthropogenic and pyrogenic sources co-emit metals and acidic species (i.e., sulfur dioxide (SO 2 ) and nitrogen oxides), which enhance the acidity of particulate matter (PM) and bioaccessibility of aerosol Fe (i.e., the fraction of bioaccessible Fe in total aerosol Fe) by orders of magnitude. Indeed, the 2019–2020 Australian wildfires could supply pyrogenic Fe with higher bioaccessibility than lithogenic Fe and trigger widespread phytoplankton growth in high-nutrient, low-chlorophyll (HNLC) regions of the Southern Ocean. ,, Meanwhile, individual particle observations confirm that more than 65% of nanosized Fe-containing particles are internally mixed with sulfates and nitrates over eastern China . Thus, nanoparticulate Fe oxides in anthropogenic aerosols are substantially transformed into bioaccessible Fe under acidic conditions during the aerosol lifetime. ,, At the same time, inhalation of Fe and copper (Cu) in PM 2.5 (particulate matter less than 2.5 μm in diameter) causes a variety of adverse health effects due to the formation of reactive oxygen species through the Fenton reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Since the sources of anthropogenic and lithogenic PM need to be identified for efficient and effective control strategies of air quality management, most previous studies have investigated the source apportionment of PM over urban and industrial areas in the Northern Hemisphere . Over a megacity in eastern China, the receptor model suggests that industrial emissions contribute less than 20% to PM 2.5 but are the major contributor to bioaccessible Fe (44–72%) . Consequently, bioaccessible Fe in aerosols from anthropogenic sources are substantially delivered to the northwestern Pacific. At the same time, some countries in the Southern Hemisphere such as Zambia and Chile are heavily polluted by SO 2 and trace metals from the mining industry. , Indeed, ship-based observations over the tropical Pacific have suggested influences of smelting emissions on bioaccessible metal concentrations across the eastern Pacific, with enhanced concentrations near the smelting facilities. , However, Fe emission estimates from metal production remain highly uncertain, and its inclusion in the emission inventory could increase anthropogenic Fe source flux in the fine aerosols by an order of magnitude (Table S1 ,, ).…”
Section: Introductionmentioning
confidence: 99%